Product development a structured approach to consumer product development, design, and manufacture - Mital, Anil
No longer can companies afford to keep the product design team working in isolation from the production and manufacturing team, not to mention the financial and accounting team. This book guides readers in how to develop a holistic, integrated team approach to product development.